Adolescent depression and the use of services and psychotropic medications in relation to family structure and race/ethnicity. (November 2018) - Zhang, Saijun; Smith, Douglas C.; Tabb, Karen M.
Abstract: The study examines how family structure and race/ethnicity are jointly associated with the discrepancy of adolescent past-year Major Depressive Episode (MDE) rates and the use of mental health services and psychotropic medications. Results through analyzing data from the National Survey on Drug Use and Health (2009–2016, N  = 131, 777) show that past-year MDE rates were low for adolescents in two-parent families (9.68%) relative to those in one-parent (11.09%) and non-parent families (12.26%, p  < .001). Among adolescents with past-year MDE, the odds of receiving specialty mental health services and psychotropic medications for those in one-parent (AOR = 1.41, CI = 1.24–1.6 for specialty services; AOR = 1.32, CI = 1.12–1.56 for psychotropic medications) and non-parent (AOR = 1.38, CI = 1.07–1.77 for specialty services; AOR = 1.99, CI = 1.44–2.74 for psychotropic medications) families were substantially higher than those in two-parent families after controlling for covariates. Noticeable racial/ethnic differences existed in the family structure related variation. The results suggest that policies and practices need to be responsive to the fact that adolescents in single and non-parent families generally are at a higher risk of depression and those with a past-year MDE have an unbalanced use of psychotropic medications across race and family structure. Highlights: Family structure is associated with adolescent risk of depression. Family structure is associated with adolescent mental health service and psychotropic medication use. Race/ethnicity interacts with family structure in relation to adolescent risk of depression and service use.